IGH gene rearrangement in Acute Lymphoid Leukemia: A study from western region of India - M. Kazi, Mahnaz; Trivedi, Pina J.; M. Patel, Dharmesh; K. Varma, Priya; Patel, Archana (International Journal of Scientific Research in Biological Sciences, 2022)
Acute lymphoblastic Leukemia (ALL) is found to be a heterogeneous disorder that coexists with multiple clones. The treatment and outcome of ALL is dependent on risk stratifications of ALL patients that is decided on the basis of prognostic factors such as WBC count, age, immunophenotype and cytogenetic aberrations. There are about 75% of ALL patients that harbors recurring chromosomal aberrations out of which 5% had IGH gene rearrangement. This rearrangement can be detected by Fluorescence in situ Hybridization (FISH). The present work was conducted for studying the prevalence of IGH gene rearrangement and to correlate it with prognostic factors and survival. In the present study, blood, and bone marrow of newly diagnosed 50 ALL patients were included. Molecular cytogenetic method i.e., FISH was used to identify rearrangement in IGH gene present on chromosome 14q32 using IGH break apart probe. The results were statistically analyzed using SPSS software and were considered statistically significant when p value ? 0.05. In the present study, 14 (28%) patients had signal pattern other than 2F. Among 14 patients with abnormal signal pattern, 9 (18%) had rearrangement of IGH gene (OGF), 4 (8%) had gain of IGH gene (FFF/FFFF) and 1 (2%) had loss of IGH gene (F). IGH gene rearrangement and IGH gene abnormality (IGH gene rearrangement, IGH gene gain and IGH gene loss) was found to be significantly associated with B-ALL subtype. Also, IGH gene abnormality was significantly correlated with patients belonging to younger age group and absence of splenomegaly. Additionally, out of total 9 patients with IGH gene rearrangement, 3 (33%) patients died and all of them were of B-ALL subtype. FISH is a powerful tool to analyze cytogenetic abnormalities in patients with ALL. IGH gene rearrangement defines a genetic feature that is frequent among patients with Acute Lymphoblastic Leukemia. Moreover, patients with IGH gene rearrangement and of B-ALL subtype showed poor prognosis.